44Ca doped remineralization study on dentin by isotope microscopy. Issue 4 (April 2018) - Hiraishi, N.; Kobayashi, S.; Yurimoto, H.; Tagami, J.
Graphical abstract: Highlights: Intrinsic 40 Ca (tooth-derived mineral) and extrinsic 44 Ca (solution-derived mineral) are distinguished by 44 Ca doped pH-cycling. The isotope image of 40 Ca and 44 Ca distribution is revealed by a high mass-resolution stigmatic secondary ion mass spectrometry system. The uptake of 44 Ca (tooth-derived mineral) is great in intensity especially in the superficial lesions. When fluoride is used, 40 Ca (tooth-derived mineral) distribution is absent in the surface lesions. Abstract: Objective: The dental caries is developed as a result of an alternative course of mineral gain and loss. In order to distinguish between intrinsic Ca (tooth-derived mineral) and extrinsic Ca (solution-derived mineral) uptakes, a 44 Ca doped pH-cycling was performed using 44 Ca (a stable calcium isotope) remineralization solution. Methods: The natural abundance of 40 Ca and 44 Ca is 96.9% and 2.1%, respectively. The remineralization solution was prepared using 44 Ca to contain 1.5 mmol/L CaCl2 ( 44 Ca), 0.9 mmol/L KH2 PO4, 130 mmol/L KCl, 20 mmol/L HEPES at pH 7.0. The pH-cycling was conducted on bovine root dentin daily by demineralization (pH 5.0) for 2 h, incubation in 0% (control) and 0.2% NaF (900 ppm fluoride) for 2 h and 44 Ca doped remineralization for 20 h. After 14 days pH-cycling, the specimens were sectioned longitudinally. On the sectioned surface, isotope imaging of 40 Ca and 44 Ca labeled mineral distribution was observed by a high mass-resolution stigmatic secondary ion 77 (Camera IMS 1270, Gennevilliers Cedex, France). Results: Uptake of 44 Ca was greater in intensity for the 0.2% fluoride group than the control, especially in the superficial lesions. The control group showed 40 Ca (intrinsic) distribution in the subsurface lesions and in the superficial lesions, meanwhile the fluoride group showed 40 Ca distribution limited in subsurface lesions. The total Ca ( 44 Ca + 40 Ca) image revealed more homogeneously for the control than the fluoride group. Significance: Since the fluoride-treated surface is more acid-resistant than intrinsic dentin, alternative minerals were dissolved from the intact intrinsic lesion in the demineralization cycle.